2016
DOI: 10.1186/s13741-016-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting, preventing, and identifying delirium after cardiac surgery

Abstract: Delirium after cardiac surgery is a major problem. The exact mechanisms behind delirium are not understood. Potential pathways of delirium include neurotransmitter interference, global cognitive disorder, and neuroinflammation. Several predisposing and precipitating risk factors have been identified for postoperative delirium. The development of delirium following cardiac surgery is associated with worse outcomes in the perioperative period. Multiple interventions are being explored for the prevention and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 69 publications
0
31
0
5
Order By: Relevance
“…We also found that the QoL of elderly patients after CABG was determined by whether or not the patient developed POD and cognitive decline. Therefore, the implementations of multicomponent interventions directed at preventing POD, which includes pharmacological and nonpharmacological interventions (Gorski et al, ; O'Neal & Shaw, ), or strategies directed at reducing cognitive function decline when the patient developed POD, may improve the QoL of patients after CABG. Considering that the elderly patients continue to form an even growing proportion of the CABG population and the advanced age is a risk factor for POD and cognitive function decline (Baranyi & Rothenhausler, ; Ida & Kawaguchi, ; Sophie, ; Strom et al, ), it is vital that clinicians need to be alert to prevent both POD and cognitive function decline.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the QoL of elderly patients after CABG was determined by whether or not the patient developed POD and cognitive decline. Therefore, the implementations of multicomponent interventions directed at preventing POD, which includes pharmacological and nonpharmacological interventions (Gorski et al, ; O'Neal & Shaw, ), or strategies directed at reducing cognitive function decline when the patient developed POD, may improve the QoL of patients after CABG. Considering that the elderly patients continue to form an even growing proportion of the CABG population and the advanced age is a risk factor for POD and cognitive function decline (Baranyi & Rothenhausler, ; Ida & Kawaguchi, ; Sophie, ; Strom et al, ), it is vital that clinicians need to be alert to prevent both POD and cognitive function decline.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In a study on patients who underwent vascular surgery, Katznelson et al found an increased incidence of delirium in patients taking β blockers (26.5% vs 17.4%, p = 0.03). 3 Another study that included on-pump and off-pump CABG surgeries, valve surgery, and also patients who underwent transcatheter aortic valve implantation cardiac surgery found an association between β-blocker use and delirium (OR 1.7, 95% CI 1.1 to 2.6, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Tanı koyabilmek amacıyla yıllar içinde birçok ölçek geliştirilmişse de Ely ve ark. [10] tarafından geliştirlen Yoğun Bakım Ünitesinde Konfüzyonun Değerlendirme Ölçeği (YBÜ-KDÖ)[The Confusion Assessment Method for the Intensive Care Unit (CAM-ICU)] günümüzde klinisyenlerce kullanılan en geçerli ve güvenilir yöntem olarak tanınmaktadır. Çalışmamızda, YBÜ KDÖ ile klinik tanı alanların tanıları %100 tutmaktadır, ölçeğin sensitivitesi %100'dür.…”
Section: Discussionunclassified
“…[7][8][9] tarafından yoğun bakımda konfüzyonun değerlendirilmesi amacıyla Yoğun Bakım Ünitesinde Konfüzyonun Değerlendirme Ölçeği (YBÜ-KDÖ) [The Confusion Assessment Method for the Intensive Care Unit (CAM-ICU)] geliştirilmiştir (Şekil 1). Bu test günümüzde de klinisyenlerce kullanılan en geçerli ve güvenilir yöntem olarak tanınmaktadır [10] .…”
unclassified